What my mother doesn't know - Sones, Sonya (New York : Simon & Schuster Books for Young Readers, 2001)
Sophie describes her relationships with a series of boys as she searches for Mr. Right.
A novel.
920
Accelerated Reader AR
Keywords: Dating (Social customs) -- Fiction; Love -- Fiction